Lung recruitment maneuver improves right and left ventricular function in patients with acute respiratory distress syndrome - Alexis Lambour; Yoann Zerbib; Pablo Mercado; Loay Kontar; Bertrand De Cagny; Julien Maizel; Michel Slama; Clément Brault (BMC Pulmonary Medicine)
Abstract Background Lung recruitment maneuvers (LRM) and high positive end-expiratory pressure (PEEP) may benefit some patients by reopening non- or poorly aerated alveoli. However, the effects of opening the lung with LRM on hemodynamics remain uncertain. This study aimed to evaluate the direct impact of LRM on cardiac function in patients with moderate-to-severe acute respiratory distress syndrome (ARDS). Methods This post-hoc analysis included 34 patients with moderate-to-severe ARDS from two prospective cohort studies. The LRM consisted in a gradual increase in PEEP, starting from 25 cmH2O (PEEPpre, before the recruitment maneuver at PEEP 25 cmH2O) until reaching 40 cmH2O. After LRM, PEEP was decreased to 25 cmH2O (PEEPpost, after the recruitment maneuver, also at PEEP 25 cmH2O) followed by a decremental PEEP titration. We compared the size and function of the right ventricle (RV) and left ventricle (LV) between PEEPpre and PEEPpost. Results The respiratory system compliance significantly increased from 21 ± 7 ml/cmH2O at PEEPpre to 24 ± 7 ml/cmH2O at PEEPpost (p < 0.001), indicating effective lung recruitment. The RV end-diastolic diameter and the RV/LV ratio decreased after LRM (51 ± 11 vs. 41 ± 9 mm; p < 0.001, and 1.05 ± 0.21 vs. 0.90 ± 0.18; p < 0.001, respectively), suggesting reduced pulmonary vascular resistance. The RV free wall strain improved from -22 ± 10 to -25 ± 8% (p = 0.040). The cardiac index significantly increased from 2.1 ± 0.6 to 2.4 ± 0.7 L/min/m2 (p < 0.001) due to improved LV function, as demonstrated by a lower LV global longitudinal strain at PEEPpost (-16 ± 4% vs. -19 ± 3%, p = 0.002). Conclusions LRM may benefit both the lungs and the heart. The increase in transpulmonary pressure leads to an expansion in aerated lung volume, potentially reducing lung overdistension and collapse, thereby lowering RV afterload and improving RV systolic function.